Compassionate care during the COVID-19 pandemic - Jing Jing Su; Jonathan Bayuo; Rose S.Y. Lin; Arkers Kwan Ching Wong; Hammoda Abu-Odah; Qijun He; Ladislav Batalik (BMC, 2024)
Abstract Background There was a substantial documented call for healthcare professionals to provide compassionate care during the COVID-19 pandemic and significant criticism voiced when it was lacking. This study aimed to explore perspectives on compassionate care among healthcare professionals providing care during the COVID-19 pandemic. The study focuses on healthcare professionals who participated in a wide range of COVID-19 measures, including testing, quarantine, diagnosis, and care provision (patients with COVID-19 or patients with other illnesses and comorbid with COVID-19). Methods A qualitative design with an interpretative phenomenological analysis approach was used. Twenty frontline healthcare professionals (15 nurses and five physicians) who had worked in COVID-19 facilities in China were interviewed individually. Results Participants stated that a commitment to 'offering oneself' and 'balancing the advantages/disadvantages' in providing care during the pandemic were key to alleviate population-level suffering. On a personal level, they described a desire for obtaining 'mutual support' and improving 'professional competencies' to safeguard their physical and mental well-being. Two professional competencies were notable: coping with grief and implementing infection control across the organization. Additionally, they emphasized the importance of receiving support from the health care organization, the public, and leaders in creating an 'environment conducive to fostering compassionate care.' Conclusion Healthcare professionals recognized the centrality of compassionate care during the pandemic which entailed a commitment to offering themselves, the balancing of advantages and disadvantages in order to find the best solution, as well as the need to safeguard themselves using professional competencies. Such findings can enrich the contemporary understanding of compassion, including when it is lacking. Support from the healthcare organization, the public, and leadership were crucial in fostering compassionate care in healthcare professionals during the pandemic and in moving the field forward in the future.